Uji Toksisitas Subkronis Fraksi Etil Asetat Kulit Buah Asam Kandis (Garcinia cowa Roxb.) terhadap Fungsi Hati dan Ginjal Mencit Putih Betina - Fatma Sri Wahyuni; Intan Nedia Putri; Dessy Arisanti (Fakultas Farmasi Universitas Andalas, 2017)
The sub-chronic toxicity testing of ethyl acetate fraction of fruit rind of “asam kandis” (Garcinia cowa Roxb.) to the liver and kidney function has been carried out to female white mice. A total of 18 female white mice aged 2-3 months weighing 20-30 grams are used as test animals. Animals were divided into three groups: one control group and two treatment groups. Groups were given daily ethyl acetate fraction at the doses of 500 and 1000 mg/kg orally for 60 days. Parameters observed were the activity of SGPT and liver weight ratio to observe the liver function; serum creatinine level and kidney weight ratio to determine kidney function. Data of SGPT, serum creatinine and the weight ratio of liver and kidney were analyzed by two-way ANOVA. Results show that the activity of SGPT and serum creatinine level were directly affected by the dose (p<0.05), while the organ weight ratio of liver and kidney were not affected by the dose and duration of administration (p>0.05). The study concluded that the dosage of ethyl acetate fraction of the fruit rind of G. cowa had a significant effect on the activity of SGPT and serum creatinine level of female white mice. The duration of administration did not give a significant effect on the increase of serum creatine level as well as the organ weight ratio of liver and kidney of mice.